2023
DOI: 10.1038/s41598-023-29839-8
|View full text |Cite
|
Sign up to set email alerts
|

Taguchi optimization and modelling of stir casting process parameters on the percentage elongation of aluminium, pumice and carbonated coal composite

Abstract: Aluminium matrix composites, which are a subclass of metal matrix composites, have characteristics including low density, high stiffness and strength, better wear resistance, controlled thermal expansion, greater fatigue resistance, and improved stability at high temperatures. The scientific and industrial communities are interested in these composites because they may be used to manufacture a broad variety of components for cutting-edge applications. This has study observed how the stirring speed, processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Aluminum (Al), iron (Fe), silicon (Si), and magnesium (Mg) are the peaks for the EDS analysis shown in figure 4(b). These elements confirmed that the alloy used was Al 6061 alloy, which validated the results of the XRF analysis and agreed with the findings of Ibrahim et al (2023b).…”
Section: Scanning Electron Microscopy With Energy Dispersive X-ray An...supporting
confidence: 88%
“…Aluminum (Al), iron (Fe), silicon (Si), and magnesium (Mg) are the peaks for the EDS analysis shown in figure 4(b). These elements confirmed that the alloy used was Al 6061 alloy, which validated the results of the XRF analysis and agreed with the findings of Ibrahim et al (2023b).…”
Section: Scanning Electron Microscopy With Energy Dispersive X-ray An...supporting
confidence: 88%
“…The fabrication route selected should be cost-effective and should ensure a uniform distribution of the selected particles within the matrix. Liquid state processing such as melt stir casting is considered to be an effective method to fabricate particulatereinforced AMCs [32,33]. Stir casting is one such processing route which has universal commercial acceptability to fabricate AMCs owing to its flexibility, ability to cast intricate geometries and cost-effectiveness [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has demonstrated that there is no significant difference in quality between virgin and recycled aluminum alloys. Moreover, incorporating aluminum scraps in the green manufacturing of aluminum alloys/composites for engineering applications offers two advantages: substantial reductions in energy consumption and decreased greenhouse gas emissions associated with primary aluminum production from ore [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%